PENGARUH KETERLIBATAN KONSUMEN DALAM KOMUNITAS MEREK ONLINE TERHADAP KECINTAAN MEREK DAN REKOMENDASI POSITIF - Djaganata, Alodiazada Nurihda; Riorini, Sri Vandayuli; Jelita Rizki Widyowati; Indahyanti, Tri (Institut Shanti Bhuana, Program Studi Kewirausahaan, 2024)
This research explores the relationship between Brand Love, Consumer Engagement, Brand Relationship Quality, Consumer Community Identification, and Positive Word-of-Mouth (WOM) on online shopping platforms, involving the participation of 150 users. Employing a quantitative approach, the study utilizes a questionnaire as the data collection instrument. Findings reject the influence of Brand Relationship Quality and Consumer Community Identification on Consumer Engagement. Conversely, the research reveals a positive relationship between Brand Love and Positive Word-of-Mouth, as well as between Consumer Engagement and Brand Love. Further analysis highlights that the level of brand affection acts as a catalyst for positive recommendations, while active consumer interactions can enhance their level of brand love. These findings underscore the importance of creating emotional connections with the brand to stimulate positive Word-of-Mouth. The study provides in-depth insights into factors influencing WOM on online shopping platforms, potentially supporting the development of more effective marketing strategies. Involving 150 respondents, the research holds practical implications in the current digital and global context. The quantitative method using a questionnaire, data validity, and reliability confirmed through SPSS 21, along with goodness-of-fit (GOF) analysis and hypothesis testing using Amos 23, establishes a robust methodological foundation. Research ethics principles, including consent and data anonymization, are upheld to maintain the integrity and security of respondent information.